2018
DOI: 10.1093/infdis/jiy588
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Cerebrospinal Fluid Bacterial Load Correlates With Inflammatory Response and Predicts Neurological Events During Tuberculous Meningitis Treatment

Abstract: In tuberculous meningitis (TBM), a higher pretreatment CSF bacterial load was associated with increased disease severity and host inflammation. The bacterial load can be used to predict new neurological events but not death. Owing to the divergent pathogenesis of TBM-associated neurological complications and deaths, strategies to reduce them may need reassessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
1
25
0
6
Order By: Relevance
“…The sensitivity of both assays was higher in HIVinfected than in HIV-uninfected individuals, probably reflecting the larger numbers of bacteria in CSF samples from these patients. 19 Additionally, Xpert Ultra appeared to be able to detect more patients with tuberculous meningitis with very low or trace levels of bacteria in their CSF and to be more sensitive than Xpert once antituberculosis treatment had been started. Previous studies have suggested that Xpert Ultra is significantly more sensitive than Xpert for the diagnosis of tuberculous meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of both assays was higher in HIVinfected than in HIV-uninfected individuals, probably reflecting the larger numbers of bacteria in CSF samples from these patients. 19 Additionally, Xpert Ultra appeared to be able to detect more patients with tuberculous meningitis with very low or trace levels of bacteria in their CSF and to be more sensitive than Xpert once antituberculosis treatment had been started. Previous studies have suggested that Xpert Ultra is significantly more sensitive than Xpert for the diagnosis of tuberculous meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Thuong et al . found that among 692 Vietnamese adults with TBM, pre-treatment CSF M.tb load (by Xpert Ct) was correlated with increased CSF neutrophil counts, increased cytokine production, and new neurological events after treatment initiation, but not death 43 .…”
Section: Tbm Pathogenesismentioning
confidence: 95%
“…TBM patients generally have low bacterial loads in CSF which causes difficulties in both diagnosis and ability to study bacterial load evolution-related pathophysiology. The time-to-positivity of a culture and cycle threshold (Ct) of nucleic acid amplification tests such as GeneXpert MTB/Rif (Xpert) can provide an indication of likely bacterial burden 43 . Over 50% of diagnosed cases are microbiologically undetectable and defined as ‘probable’ or ‘possible’ TBM which obviously limits this approach 44 .…”
Section: Tbm Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…10 Hingga saat ini, masih belum ditemukan patofisiologi yang jelas mengenai perubahan spesifik dari tiap parameter LCS, seperti yang dilaporkan oleh Thuong. 13 Pemeriksaan LCS juga dipengaruhi oleh prosedur pengambilan sampel yang kurang tepat, kadar patogen itu sendiri, dan penggunaan antibiotik yang dapat mengakibatkan hasil pemeriksaan LCS mengalami perubahan atau tampak normal. 11 Berbagai jenis infeksi yang terjadi pada tubuh manusia dapat memicu timbulnya demam atau panas badan.…”
unclassified